Rebooting in sport training and competitions: Athletes` perceived stress levels and the role of interoceptive awareness - Di Fronso, S.; Montesano, C.; Costa, S.; Santi, G.; Robazza, C.; Bertollo, M. (Journal of Sports Sciences, 2022)
The psychological consequences of the lockdown in the sport context have been well studied. However, few studies investigated athletes` perceived stress during the rebooting in sport training and competitions; moreover, no investigations examined the relationship between perceived stress and interoceptive awareness. To mind this gap and support the enactment of appropriate behaviours for practising sports in a unique situation, we compared athletes` perceived stress data collected during the rebooting in sport activities with normative data and with those collected during the first Italian lockdown. Furthermore, we examined the impact of interoceptive awareness towards positive and negative stress by means of regression analyses. The IPSS-10 and the MAIA questionnaire were administered to 220 athletes. Findings suggest that athletes were experiencing a detrimental situation despite the resumption of sport activities but when comparing rebooting phase with the lockdown, female athletes began to feel greater financial security thereby reducing their perceived stress. Athletes who scored high especially for body trusting - the experience of one`s body as safe and trustworthy - could regulate their perceived stress levels by increasing positive and reducing negative stress. Athletes could engage in mindful activities related to the body to reduce their perceived stress levels and better deal with an unprecedented situation.